Textbook Evaluation: Target Needs Analysis of Vocational Students Majoring in Hospitality - Susilowaty Susilowaty (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2019)
Textbook is one of the important elements in English language teaching. As the importance of textbook, it should reflect on the students’ needs. However, many studies revealed that most textbooks, especially ESP textbook were not satisfying and did not meet students’ needs. There were not many studies about ESP textbook evaluation in Indonesian context. The present study explored about to what extent the materials in the ESP textbook used by English teacher in teaching ESP in a particular vocational school majoring in hospitality meet the language needs in hospitality industry. Questionnaires were distributed to 24 students majoring in hospitality to explore about their needs, wants, and lacks. To confirm the students’ needs in actual workplace, semi-structured interview sessions were conducted to hotel employers. The results from questionnaire and interviews were used as the criteria to evaluate the textbook together with textbook evaluation criteria. The results revealed that the English language skills, especially English-speaking skill was important for the students from hospitality program. There were 21 hospitality competencies that needed English skills in their implementation discovered in this study. However, the materials in the textbook did not accommodate the students’ needs to improve English speaking skill. Furthermore, the textbook covered only five out of 21 hospitality competencies that were needed by hospitality students.